EKSTRAKSI PIGMEN ANTOSIANIN DARI KULIT RAMBUTAN (NEPHELIUM LAPPACEUM) DENGAN PELARUT METANOL (Talenta Publisher (Universitas Sumatera Utara), 2014)
Rambutan fruit (Nephelium lappaceum) is a kind of tropical fruits which come from Malaysia and Indonesia. Their red coloured rinds have not used yet effectively and the red coloured may be due to anthocyanin that can be used for natural colours. The purpose of this research is to know the optimal conditions of the extraction of anthocyanin, they are particle size of rambutan rind, temperature and extraction time. Analysis of the anthocyanin use spectrophotometer UV-Vis to detect the wavelength and the absorbance of the anthocyanin. The best conditions are rambutan rind milled by blender at temperature 50 0C and extraction time for 6 hours. These conditions give the highest color intensity having 1,6103 of maximal absorbancy, 55,7659 mg/mL of anthocyanin concentration and 0,2788% of rendement.